Recursos didácticos manipulativos, para fortalecer la lecto-escritura, en alumnos de tercer grado, Escuela de Educación Básica, Juan Montalvo, Pasaje, 2022 - Ortiz Mendoza, Isael Alexander; Fernandez Sisalima, Andreina Elizabeth (Machala : Universidad Técnica de Machala, 2023)
The use of didactic resources within the teaching and learning process is of the utmost importance in its development, since they allow to simplify the work in the classroom, since they are an effective tool to improve the teacher-student relationship. Its usefulness is highlighted, since they can be adapted to the context and there are various materials for various subjects, this has caused traditional education to be progressively left aside, although not in its entirety since it can still be evidenced from the educational field. Even the passive and traditional teaching role, although it does not use new teaching methodologies. The data was obtained by conducting an interview with the 2 teachers in charge, an interview with 44 students and the approach of an observation guide to teacher performance and student performance, all these instruments were applied with the intention of knowing how had been developing the process of teaching and learning literacy in the subject of language, resulting in the lack of application of materials within the teaching methodology, based solely on the use of textbooks, blackboard and resorting to dictation as strategy, considering traditional methodologies and lack of innovation, which without detracting from their effectiveness, can be complemented with new dynamic resources, therefore, it was decided to develop a methodological guide with manipulative teaching resources that arouse the interest and motivation of the student body for learn to read and write, promoting an interactive learning space live and dynamic
La utilización de recursos didácticos dentro del proceso de enseñanza y aprendizaje, es de suma importancia en el desarrollo del mismo, puesto que, permiten simplificar el trabajo áulico, pues son una herramienta eficaz para mejorar la relación docente-alumno. Se resalta su utilidad, porque se los puede adecuar al contexto y existen diversos materiales destinados a diversas asignaturas, esto ha provocado que se pueda dejar de lado progresivamente la educación tradicional, aunque no en su totalidad ya que aún se puede evidenciar desde el campo educativo mismo el rol docente pasivo y tradicional, mismo que no utiliza nuevas metodologías de enseñanza. Es por esta razón que se ha visto la necesidad de realizar la investigación sobre los diversos recursos didácticos manipulativos utilizados en el fortalecimiento de la lectoescritura, en el tercer grado de la escuela “Juan Montalvo”, cantón Pasaje periodo 2022-2023. Para llegar al planteamiento del problema y por ende a la selección del tema en cuestión, se procedió a realizar una observación directa del proceso educativo llevado a cabo dentro de la institución mencionada anteriormente. Esta investigación ha sido realizada recurriendo a un enfoque mixto (cuanti-cualitativo), pues, se obtuvo información mediante la observación directa de campo, misma que fue tabulada y representada a través de cuadros y gráficos estadísticos.
Keywords: RECURSO DIDACTICO MANIPULATIVO; LECTOESCRITURA; DOCENTE; ENSEÑANZA-APRENDIZAJE